2016
DOI: 10.2188/jea.je20150095
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Total and Domain-Specific Sedentary Time With Type 2 Diabetes in Taiwanese Older Adults

Abstract: BackgroundThe increasing prevalence of type 2 diabetes in older adults has become a public health concern. We investigated the associations of total and domain-specific sedentary time with risk of type 2 diabetes in older adults.MethodsThe sample comprised 1046 older people (aged ≥65 years). Analyses were performed using cross-sectional data collected via computer-assisted telephone-based interviews in 2014. Data on six self-reported domains of sedentary time (Measure of Older Adults’ Sedentary Time), type 2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 34 publications
3
31
1
Order By: Relevance
“…Our results are also consistent with those from Healy and colleagues, 17 who found that among a subsample of the AusDiab study that wore an accelerometer for 7 days (n = 169), 57% of their day was spent sedentary. More recently, Healy et al 30 31 Given that collectively our participants spent the majority (97%) of their time either sedentary or in LPA, we could suggest that adults with type 2 diabetes should redistribute their sedentary behaviours in favour of fewer prolonged bouts. In addition, we found significant associations between sedentary time/LPA and sex, increasing BMI, employment status, and income.…”
Section: Discussionmentioning
confidence: 75%
“…Our results are also consistent with those from Healy and colleagues, 17 who found that among a subsample of the AusDiab study that wore an accelerometer for 7 days (n = 169), 57% of their day was spent sedentary. More recently, Healy et al 30 31 Given that collectively our participants spent the majority (97%) of their time either sedentary or in LPA, we could suggest that adults with type 2 diabetes should redistribute their sedentary behaviours in favour of fewer prolonged bouts. In addition, we found significant associations between sedentary time/LPA and sex, increasing BMI, employment status, and income.…”
Section: Discussionmentioning
confidence: 75%
“…Our findings have extended these works by showing the associations in an Asian population. In addition, several studies have shown an association between self-reported sitting time and the presence of diabetes mellitus 8,14,27,28 . The present findings support the notion that prolonged sedentary time increases the risk of having diabetes independent of physical activity levels.…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, conclusive evidence has indicated that 2 h of TV viewing per day serves a reasonable cutoff point, with more than 2 h per day having been clearly associated with deleterious health outcomes [ 7 ]. Several previous studies have shown viewing more than 2 h of TV per day is associated with increased risk of overweight [ 8 , 9 ] and type 2 diabetes [ 10 ]. Despite these adverse consequences, a recent study found that nearly half (47.4%) of older adults in Taiwan engage in excessive TV viewing time (≥2 h/day) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%